Wheat Grain Yield Response to Seed Cleaning and Seed Treatment as Affected by Seeding Rate During the 2018–2019 Growing Season in Kansas - R. P. Lollato; K. Mark; B. R. Jaenisch; L. Haag (Kansas Agricultural Experiment Station Research Reports, 2020)
The objective of this project was to evaluate winter wheat stand count and grain yield responses to the interactions among seeding rate, seed cleaning, and seed treatment in the state of Kansas during the 2018–2019 growing season. Experiments evaluating the response of the wheat variety “SY Monument” to three seeding rates (600,000, 900,000, and 1,200,000 seeds per acre), three seed cleaning intensities (none, air screen, and gravity table), and two seed treatments (none and insecticide + fungicide) were established in a split-split plot design conducted in a complete factorial experiment at seven Kansas locations. In-season measurements included stand count, grain yield, grain test weight, and grain protein concentration, though this report only shows stand count and grain yield. Stand count increased with increases in seeding rate at all locations, with improvements in seed cleaning in five locations, and by seed treatment in one location. Grain yield increased with increases in seeding rate in five locations, with improvements in seed cleaning in four locations, and with seed treatment in one location. Significant interactions on grain yield occurred between seeding rate and seed cleaning (one location) and seeding rate and seed treatment (two locations), usually suggesting an advantage for seed cleaning or seed treatment at low seeding rates. The combined analysis across locations suggested that seeding rate and seed cleaning improved stand count ( 140,000 and 35,000 more plants established for each level of seeding rate and seed cleaning improvement) and grain yield (about 5 and 2 more bushels per acre for each improvement in seeding rate and seed cleaning, respectively). This research is an initial step in evaluating the value of the seed certification process; it does not compare certified seed versus bin-run seed. The seed used in this study derived from commercial seed production fields (i.e., high quality seed) and not from commercial grain production fields, which usually provide bin-run seed.
Keywords: wheat; seed cleaning; seed treatment; seeding rate